2011
DOI: 10.1111/j.1526-4637.2011.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization of Patients with Chronic Pain: The Extinction of Empathy

Abstract: Greater awareness by health professionals of their own potential, often inadvertent, contribution to the stigmatization of their patients with chronic pain may serve as a basis for an expanded model of clinical engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 46 publications
3
87
0
Order By: Relevance
“…Given that professional healthcare providers have insufficient knowledge about the nature of chronic nonmalignant pain [75], or report feeling less effective and uncertain when treating patients with chronic pain [63], the first step would be to enhance knowledge of chronic pain through pain education [5,8,39,57]. Extending the narrow biomedical perspective on acute pain to the comprehensive biopsychosocial model would compel consideration of a broader range of determinants of pain related disability [2,5].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Given that professional healthcare providers have insufficient knowledge about the nature of chronic nonmalignant pain [75], or report feeling less effective and uncertain when treating patients with chronic pain [63], the first step would be to enhance knowledge of chronic pain through pain education [5,8,39,57]. Extending the narrow biomedical perspective on acute pain to the comprehensive biopsychosocial model would compel consideration of a broader range of determinants of pain related disability [2,5].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…to the scientific literature (Bove 2008, Bove 2009, Quintner and Bove 2001, Cohen et al 2013, Cohen et al 2011, Quintner et al 2008. In this paper, they criticize the hypothesis of TrP formation as put forth initially by Simons and Travell, and later modified by others (Gerwin et al 2004, Simons 1996, McPartland 2004, McPartland and Simons 2006.…”
Section: Quintner Bove and Cohen Have Made Significant Contributionsmentioning
confidence: 90%
“…Chibnall et al [29] found that between-physician consistency was very low for the diagnosis of CP. Due to the lack of specific diagnostic tests to assess the organic pathology of CP, patients may even be labelled as somatizers or even malingerers [30,31]. Chronic pain patients often feel that the absence of a discernible diagnosis implies that health professionals feel that the pain may just be in their minds [32].…”
Section: Discussionmentioning
confidence: 99%